SMA1, a homolog of the splicing factor Prp28, has a multifaceted role in miRNA biogenesis in Arabidopsis. Issue 17 (30th June 2018) - Li, Shengjun; Xu, Ran; Li, Aixia; Liu, Kan; Gu, Liqing; Li, Mu; Zhang, Hairui; Zhang, Yueying; Zhuang, Shangshang; Wang, Quanhui; Gao, Gang; Li, Na; et al.
Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that repress gene expression. In plants, the RNase III enzyme Dicer-like (DCL1) processes primary miRNAs (pri-miRNAs) into miRNAs. Here, we show that SMALL1 (SMA1), a homolog of the DEAD-box pre-mRNA splicing factor Prp28, plays essential roles in miRNA biogenesis in Arabidopsis. A hypomorphic sma1-1 mutation causes growth defects and reduces miRNA accumulation correlated with increased target transcript levels. SMA1 interacts with the DCL1 complex and positively influences pri-miRNA processing. Moreover, SMA1 binds the promoter region of genes encoding pri-miRNAs ( MIR s) and is required for MIR transcription. Furthermore, SMA1 also enhances the abundance of the DCL1 protein levels through promoting the splicing of the DCL1 pre-mRNAs. Collectively, our data provide new insights into the function of SMA1/Prp28 in regulating miRNA abundance in plants.